The Influence of Social Change, Media Management, Transformational Leadership Style, With Commitment As a Mediating Variable On Public Trust in Polda Metro Jaya - Teddy Rachesna (International Forum of Researchers and Lecturers, 2026)
Background: This study aims to examine the influence of social change, media management, and transformational leadership on public trust, both directly and indirectly through organizational commitment. This research contributes to the development of public trust theory by highlighting the essential mediating role of organizational commitment in strengthening the impact of leadership, communication, and social dynamics within public institutions Using a quantitative approach with Structural Equation Modeling (SEM) and the Partial Least Squares (PLS) method, the research collected data through surveys administered to respondents within public service organizationsThe results show that social change, media management, and transformational leadership significantly influence public trust, with organizational commitment acting as a mediating variable. Social change and media management impact public trust indirectly through organizational commitment, while transformational leadership directly and indirectly influences commitment and public trust.This study is limited by its specific institutional scope, indicating the need for further research involving wider populations and diverse public service settings. Practically, the findings suggest that public organizations need to prioritize adaptive leadership, effective internal and external media management, and responsive strategies to social changes in order to strengthen organizational commitment and build sustainable public trust